Study of the fluorescence quenching of 1-hydroxypyrene-3,6,8-trisulfonic acid by single-walled carbon nanotubes - Herminsul Cano (Universitas Scientiarum)
This paper presents a study of the fluorescence quenching of 1-hydroxypyrene-3,6,8-trisulfonic acid (HPTS) in the presence of single-walled carbon nanotubes (SWCNT) using a fluorescence method. To investigate the quenching mechanism (dynamic or static) of HPTS, Stern-Volmer plots of single walled carbon nanotubes at different temperatures were used. The positive deviation from linearity in Stern-Volmer plots suggests that single walled carbon nanotubes follow a static quenching mechanism evidenced by the formation of a stable ground state complex. The results presented here help us to clarify the quenching mechanism in the interaction of a pyrene derived dye and carbon nanotubes. This study will open new possibilities in the use of the conjugate formed by SWCNTs and HPTS in the fabrication of a biosensor based on intracellular fluorescent probes.